Orchestrating warfighting : a history of the British Army's corps and divisions at war since 1914 - Bean, Tim; Flint, Edward R. (Edward Rupert), 1969-; Kitchen, James E.; Latawski, Paul C. (Paul Chester), 1954- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Orchestrating Warfighting provides a detailed and wide-ranging examination of the employment of corps and divisions from the First World War through to the early twenty-first century. Orchestrating Warfighting examines British, Dominion, and imperial corps and divisions, taking part in the total wars of the first half of the twentieth century and smaller scale conflicts since 1945. It throws new light on questions of command, generalship, and the management of battles and campaigns across a diverse range of theatres. Orchestrating Warfighting is of interest to historians of the British Army, operational military history, and modern war"--
The British Army's Corps and Divisions at War since 1914 : Histories of Command and the Operational Level of War / James E. Kitchen -- The British Corps and Division in the Twentieth Century : Historical Evolution and Doctrinal Context / Paul Latawski -- Imperial Warfighting : British and Empire Corps Command on the Western Front, 1914-18 / Andy Simpson -- The Indian Corps on the Western Front, 1914-15 / Kaushik Roy -- Engines of War : Supply and Transport in the Canadian Corps on the Western Front, 1914-16 / Andrew Iarocci -- British Army, Corps, and Divisional Command on the Somme : Planning and Executing the Attack on the Leipzig Salient, 3 July 1916 / Stuart Mitchell -- Almost a British Division? The New Zealand Division on the Western Front, 1916-18 / Christopher Pugsley -- 'A sound and definite organization' : The Egyptian Expeditionary Force and Corps Planning for the Third Battle of Gaza, October-November 1917 / James E. Kitchen -- Command in the 4th Indian Division in North Africa, 1940-43 / Kaushik Roy -- 'A man's first battle is always his best' : Douglas Wimberley, the 51st Highland Division, and the Battle of El Alamein / Christopher Mann -- Indian Army Divisions in Italy, 1943-45 / Alan Jeffreys -- Freyberg and 2nd New Zealand Division / Christopher Pugsley -- British and Canadian Corps Command during the 1944-45 North-West Europe Campaign / Stephen Ashley Hart -- Corps Command in Fourteenth Army : IV (British) and XXXIII Indian Corps at the Battles of Imphal and Kohima / Tim Bean -- Orchestrating the Oboe Concerto : Planning and Command in I Australian Corps for the Borneo Campaign / Garth Pratten -- Corps Commanders in the British and Indian Armies, 1944-45 / Mark Frost -- The British-led 1st Commonwealth Division in the Korean War, 1951-54 / Paul Latawski -- Divisional Operations in the Gulf Wars / Robert Johnson -- The Future of the Divisional and Corps Echelon in British Warfighting / Jack Watling -- Corps and Divisional Warfighting : Themes and Omissions / James E. Kitchen.
Keywords: Great Britain. -- Army -- History; Operational art (Military science); Great Britain -- History, Military -- 20th century; Great Britain -- History, Military -- 21st century; HISTORY / Military / World War I; HISTORY / Modern / 20th Century; HISTORY / Military / World War II